Application of Natural Growth Regulator on Viability of Soursop Seeds (Annona Muricata Linn.). - Ismail Marzuki; T. Irmansyah; Sitepu, Ferry (Talenta Publisher, 2021)
Soursop (Annona Muricata Linn.) is a plant that has hard seeds that inhibits germination. One way that can be done to accelerate the process of germination of soursop is by scarifying and using natural growth regulators. This research aim was to identify the effect of scarification and immersion of natural growth regulators on the viability of soursop seeds. This research was conducted at the USU Faculty of Agriculture from July to September 2018 by using a Completely Randomized Design of two treatment factors namely, (1) Scarification (without scarification / control and scarification) and (2) Immersion of Natural Growth Regulators (No Immersion / Control, Immersion with young coconut water; red onion extract and young coconut water). The scarification treatment and immersion of young coconut water and/or red onion extract gave the highest yield, significantly on plant height, leaf number and vigor index.